Identification and Characterization of a Potential Probiotic, Clostridium butyricum G13, Isolated from the Intestine of the Mud Crab (Scylla paramamosain) - Huifen Liang; Ngoc Tuan Tran; Taoqiu Deng; Jinkun Li; Yifan Lei; Mohammad Akibul Hasan Bakky; Ming Zhang; Rui Li; Wenxuan Chen; Yueling Zhang; Xiuli Chen; Shengkang Li (Microbiology Spectrum, 2023)
ABSTRACT The butyrate-producing bacterium Clostridium butyricum has been proven to be important in improving the growth and health benefits of aquatic animals. In this study, C. butyricum G13 was isolated for the first time from the gut of the mud crab (Scylla paramamosain). The results of this study showed that C. butyricum G13 could produce a high concentration of butyric acid and grow well in a wide range of pHs (4 to 9) and NaCl (1 to 2.5%) and bile salt (0.2 to 1.0%) concentrations. In vitro characterization revealed that C. butyricum G13 is a Gram-positive and gamma-hemolytic bacterium sensitive to most antibiotics and shows hydrophobicity and the capacity to degrade starch. In vitro fermentation using mud crab gut contents showed that C. butyricum G13 alone or in combination with galactooligosaccharides (GOS) and/or resistant starch (RS) significantly increased butyric acid production and beneficially affected the abundance and diversity of intestinal microbiota. In addition, C. butyricum G13 can improve the survival rate of mud crabs and effectively maintain the normal structure of gut morphology after infection with Vibrio parahaemolyticus. In conclusion, C. butyricum G13 can be considered a potential probiotic that improves the immune capacity and confers health benefits on mud crabs. IMPORTANCE With the development of society, more and more aquatic animals are demanded. Intensification in the aquaculture scale is facing problems, such as disease outbreaks, eutrophication of water bodies, and misuse of antibiotics. Among these challenges, disease outbreak is the most important factor directly affecting aquaculture production. It is crucial to explore new approaches effective for the prevention and control of diseases. Probiotics have been widely used in aquaculture and have shown beneficial effects on the host. In this study, the butyrate-producing bacterium Clostridium butyricum G13 was isolated for the first time from the intestine of the mud crab through in vitro fermentation. The bacterium has probiotic properties and changes the gut microbiota to be beneficial to hosts in vitro as well as protecting hosts from Vibrio parahaemolyticus infection in vivo. The outcomes of this study indicate that C. butyricum G13 can be used as a potential probiotic in mud crab aquaculture.